Language Maintenance Through Comic Strips - Ayu Ida Savitri (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2019)
AbstractLanguage, both spoken and written, is an evidence of human civilization as it tells the culture of its users. A language extincts when its speakers were also gone without passing it into their future users. Or else, their descendants shift their language to another so that the previous one is no longer used. The extinction of many indigenous languages in Indonesia shows that their users choose to use another languages that give them more benefit than those indigenous languages. For example, instead of using indigenous languages as their mother tounge, Javanese people choose Indonesian (the official language) or even English (the international language) as their first language. Language maintenance is then needed to do to preserve the languages and the culture embedded in its use. One of the ways to do it is by using it through mass media since they have strong influence toward people. This research describes indigenous language maintenance through printed mass media, particularly through comic strip on newspaper, tabloid and magazine. Comic strip is one of the sections in printed media, usually newspaper, using spoken language written on its panel that sometimes using part of indigenous language in the conversation of its characters. The writer shows how and comic strips at printed mass media indirectly preserve spoken Javanese.